Application of the Wills Act 1837 to New Zealand: Untidy Legal History - Williams, David V (Victoria University of Wellington Law Review, 2014)
The decision of Acting Chief Justice Stephen in McLiver v Macky (1856) was that the Wills Act 1837 (UK) did not apply in New Zealand because New Zealand had been annexed to the British Empire as a dependency of New South Wales. This case and its consequences were discussed in my contribution to the Victoria University of Wellington Law Review special issue in 2010 relating to the New Zealand Law Foundation’s "Lost Cases Project". It transpires that Stephen ACJ and counsel in the 1856 case were unaware of the Imperial Act Adoption Act 1839 (NSW) which applied the Wills Act 1837 (UK) to New South Wales from 1 January 1840. This article suggests that, based on the reasoning of the Judge, the 1856 decision would have been the same even if that 1839 Act had been explicitly considered. It would still have been necessary for the New Zealand Parliament to enact the English Laws Act 1858.